2018
DOI: 10.1177/0003489418812901
|View full text |Cite
|
Sign up to set email alerts
|

The Safety and Efficacy of Expiratory Muscle Strength Training for Rehabilitation After Supracricoid Partial Laryngectomy: A Pilot Investigation

Abstract: Objectives: Expiratory muscle strength training (EMST) is a safe, effective intervention that can be performed at home and may be beneficial for individuals with voice and swallowing disorders. To date there have been few studies of EMST in the head and neck cancer population, and there are no previous reports of its use after supracricoid partial laryngectomy (SCPL). The current prospective clinical pilot study was undertaken to determine the safety and efficacy of a 4-week treatment program. Methods: Six par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 35 publications
1
12
0
1
Order By: Relevance
“…In the group of partial laryngectomy patients performing EMST a significant increase in peak cough flow (L/min) was found, from below normal prior to the intervention to within normal range after training. 24 Peak expiratory flow rate also increased significantly with training in a group of elderly. 26 It is worth questioning why PEF values did not improve in the studied group of TL participants.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…In the group of partial laryngectomy patients performing EMST a significant increase in peak cough flow (L/min) was found, from below normal prior to the intervention to within normal range after training. 24 Peak expiratory flow rate also increased significantly with training in a group of elderly. 26 It is worth questioning why PEF values did not improve in the studied group of TL participants.…”
Section: Discussionmentioning
confidence: 87%
“…Their group showed reduced average MEPs at baseline. 20 Palmer et al 24 reported a good MEP at baseline in their group after partial laryngectomy and reasoned their candidates must have good pulmonary support to tolerate some amount of aspiration during recovery. We observed no changes over time for PEF outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Entre estas se incluyó a niños hipotónicos [40], pacientes con esclerosis múltiple [41,42] y otros con enfermedad de Parkinson [36,37]. Además, se contó con problemas de voz auto-reportados [43], cáncer laríngeo con estado de post laringectomía parcial [44], quejas de profesores [45], trabajadores de la medicina con fatiga vocal [46] y lo que se denominó profesionales de la voz con disfonía [47,48]. En el grupo de habilitación o entrenamiento vocal solo 2 artículos pudieron ser considerados.…”
Section: Efectos Del Emr En La Vozunclassified